Penguatan Literasi dan Strategi Deseminasi Efektif untuk Meningkatkan Kapasitas Mahasiswa Indonesia di Thailand - Septiyanti, Nisa Dwi; Sujatmiko, Bambang; Basatha, Rizky; Akbar, Muhammad Sonhaji; Elfaiz, Ersha Aisyah; Wardah, Elvira; Habibi, Mohammad Wildan; Prayoga, Riza Akhsani Setyo; Zulatifa, Nelani Shafatia (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2026)
This community service program aimed to strengthen digital literacy and enhance effective information dissemination skills among Indonesian students in Thailand. The program was an implementation of the Tri Dharma Perguruan Tinggi by lecturers from the Information Technology Education Study Program, Universitas Negeri Surabaya. The results of the activity showed that the participants, Indonesian students in Thailand, already possessed a good level of digital literacy. Through this program, they gained a deeper understanding of the importance of applying digital literacy critically, ethically, and collaboratively, as well as realizing their strategic role as information bridges between the academic community abroad and society in Indonesia. Participants also demonstrated a strong commitment to acting as credible and integrity-driven agents of knowledge dissemination. The activity concluded with a reflection session, a group photo, and the signing of a Memorandum of Agreement (MoA) between Universitas Negeri Surabaya and the Indonesian Students Association in Thailand as a form of commitment to sustainable collaboration. Overall, this program made a tangible contribution to strengthening the culture of digital literacy, building cross-national academic networks, and reinforcing the role of Indonesian students abroad as responsible ambassadors of knowledge.